1998
DOI: 10.1091/mbc.9.4.795
|View full text |Cite
|
Sign up to set email alerts
|

Reprogramming the Cell Cycle for Endoreduplication in Rodent Trophoblast Cells

Abstract: Differentiation of trophoblast giant cells in the rodent placenta is accompanied by exit from the mitotic cell cycle and onset of endoreduplication. Commitment to giant cell differentiation is under developmental control, involving down-regulation of Id1 and Id2, concomitant with up-regulation of the basic helix-loop-helix factor Hxt and acquisition of increased adhesiveness. Endoreduplication disrupts the alternation of DNA synthesis and mitosis that maintains euploid DNA content during proliferation. To dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
153
1
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(165 citation statements)
references
References 50 publications
9
153
1
2
Order By: Relevance
“…The cyclin E-Cdk2 complex is essential for G 1 -S progression. As reported by others, we found cyclin E expression at moderate levels throughout normal placental development (20,21,30,31). We did not detect differences in the expression of cyclin E at the different stages of normal placental development.…”
Section: Discussionsupporting
confidence: 84%
“…The cyclin E-Cdk2 complex is essential for G 1 -S progression. As reported by others, we found cyclin E expression at moderate levels throughout normal placental development (20,21,30,31). We did not detect differences in the expression of cyclin E at the different stages of normal placental development.…”
Section: Discussionsupporting
confidence: 84%
“…Here, we have extended these data, showing that cyclin E is able to confer the ability to establish a re-replication cycle on di erentiating K562 cells which do not otherwise become polyploid after TPA treatment. These data are in accordance not only with the primary role of this cyclin, that is, the entrance into S phase Resnitzky et al, 1994), but also with its essential role in other re-replicating systems such as Drosophila embryonic cells (Duronio et al, 1996;Knoblich et al, 1994), maize endosperm (Gra® and Larkins, 1995), and mouse trophoblasts (MacAuley et al, 1998). Interestingly, our data also suggest that cyclin E is present in di erentiating cells undergoing re-replication cycles, in contrast with what occurs along a mitotic cycle of exponentially growing cells.…”
Section: Discussionsupporting
confidence: 73%
“…It is also expected that to undergo S phase, cells have to express cyclin A, as it has been established for proliferating cells (Ohtsubo et al, 1995;Zindy et al, 1992;Girard et al, 1991). Surprisingly, though, in other re-replicating systems including mouse trophoblasts (MacAuley et al, 1998;Sprenger et al, 1997), cyclin A appears not to be needed for extra S phases. This apparent discrepancy could be based upon fundamental di erences between the biological signi®cance of the respective re-replication cycles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…37 Studies of murine trophoblast giant cells have shown that terminal differentiation is marked by endoreduplication. 38 However we did not detect an increase in the number of polyploid SGHPL-5 cells after treatment with either CCN. Instead, our results clearly showed that both CCN proteins induced cellular senescence in SGHPL-5 cells, as demonstrated by an increased expression of SAb-gal, and the increased expression of p16, both are wellestablished markers of cellular senescence.…”
Section: Discussioncontrasting
confidence: 67%